Strategies for Supporting Inclusion and Diversity in The Academy: Higher Education, Aspiration and Inequality - Ismail, Gihan (Critical Studies in Teaching and Learning, 2023)
Crimmins, G. (ed.) 2018. Strategies for Supporting Inclusion and Diversity in The Academy: Higher Education, Aspiration and Inequality. Cham, Switzerland: Palgrave Macmillan